The effect of quantum teaching on students’ motivation on social studies (An quasi experiment for 5th grade elementary school) - Khairunnisa Khairunnisa; Yalvema Miaz; Yeni Karneli (International Conferences on Educational, Social Sciences and Technology)
This research was concerned by students’ low motivation on social studies. This research aims to determine the difference of the students’ learning motivation taught using Quantum Teaching and conventional teaching model on social studies. This research applied quasi-experiment with nonequivalent control group design. The samples were taken with simple random sampling technique, with samples as many as 44 students. Analysis of data used t-test. The result showed that the students’ motivation with Quantum Teaching were higher than conventional teaching model on social studies, where by using statistical test, the tvalue was 5,624 and ttable was 2,089 or knowable tvalue> ttable. It can be concluded that Quantum Teaching model has positive effect to improve students’ learning motivation.